PENGARUH PENGUNGKAPAN CARBON ACCOUNTING DAN ENVIRONMENTAL PERFORMANCE TERHADAP KINERJA KEUANGAN MELALUI GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BEI - Via Wahyuningtyas; Mulyanto Nugroho (Jurnal Akuntansi dan Bisnis (AKUNTANSI), 2026)
This study aims to analyse the effect of carbon accounting disclosure and environmental performance on financial performance with good corporate governance (GCG) as an intervening variable in energy sector companies listed on the Indonesia Stock Exchange for the period 2022–2024. The study uses a quantitative approach with causal methods and purposive sampling techniques, resulting in 13 companies as samples. The data were analysed using Partial Least Squares–Structural Equation Modelling (PLS-SEM) with the help of SmartPLS version 4 through outer model evaluation, inner model evaluation, and mediation effect testing. The results show that carbon accounting does not have a significant effect on financial performance, but it does have a significant effect on GCG. Environmental performance has a positive and significant effect on financial performance and GCG. Furthermore, GCG does not have a significant effect on financial performance and is unable to mediate the effect of carbon accounting or environmental performance on financial performance. These findings indicate that environmental performance has a more dominant direct effect on the financial performance of energy sector companies.